Transgender people and education - Bartholomaeus, Clare; Riggs, Damien W. (Palgrave Macmillan, 2020)
This book provides a comprehensive account of the educational experiences of students, parents, and educators--both transgender and cisgender--in the context of current debates about the inclusion of transgender people in schools. Drawing on critiques of cisgenderism and emphasizing the importance of a "whole of school" approach, Transgender People and Education explores complex topics including sexuality education for transgender young people, teaching gender diversity, the journeys of cisgender parents of transgender children, the experiences of transgender parents and educators in schools, and the role of cisgender administrators, educators, and school counselors and psychologists in creating inclusive school cultures. Reporting on empirical analyses conducted by the authors, the book makes a unique contribution to thinking about gender diversity in schools and advocates for the broadening of educational approaches beyond narrow gender binaries.1. Introduction -- 2. Transgender Young People -- 3. Cisgender Young People -- 4. Cisgender Parents of Transgender Young People -- 5. Transgender Parents and Educators -- 6. Cisgender Administrators and Educators -- 7. Cisgender School Counselors and Psychologists -- 8. Conclusion